2016
DOI: 10.18632/oncotarget.11321
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial and endoplasmic reticulum pathways involved in the apoptosis of bursa of Fabricius cells in broilers exposed to dietary aflatoxin B1

Abstract: Aflatoxin B1 (AFB1), a toxic metabolite produced by some fungi, exerts well-known hepatocarcinogenic and immunosuppressive effects, the latter can increase the apoptotic immune cells in vitro. However, it is largely unknown that which signaling pathways contribute to excessive apoptosis of immune cells which induced by AFB1. In this study, we investigated the roles of the mitochondria, endoplasmic reticulum (ER) and death receptor activated apoptotic pathways in the bursal of Fabricius (BF) cells in the broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…As for BF, this apoptotic pathway even hasn't been activated by As 2 O 3 in present study. Our result is in line with previous study which showed the expressions of Fas, FasL, FADD and caspase-8 were no difference between the Aflatoxin B 1 group and the control group, which evidenced that death receptor apoptotic pathway may not contribute to the excessive cell death of BF cells [41]. In summary, mitochondria apoptosis pathway plays a more extensive role than death receptor apoptotic pathway in chicken immune organs suffering from subchronic arsenism, and the latter pathway might be inhibited in BF cells, its exact mechanism needs further study.…”
Section: Discussionsupporting
confidence: 92%
“…As for BF, this apoptotic pathway even hasn't been activated by As 2 O 3 in present study. Our result is in line with previous study which showed the expressions of Fas, FasL, FADD and caspase-8 were no difference between the Aflatoxin B 1 group and the control group, which evidenced that death receptor apoptotic pathway may not contribute to the excessive cell death of BF cells [41]. In summary, mitochondria apoptosis pathway plays a more extensive role than death receptor apoptotic pathway in chicken immune organs suffering from subchronic arsenism, and the latter pathway might be inhibited in BF cells, its exact mechanism needs further study.…”
Section: Discussionsupporting
confidence: 92%
“…Bcl-2-shRNA inhibited the expression of the Bcl-2 gene and thereby changed the proportion of Bcl-2/Bax, thus enhancing the expression of the pro-apoptotic gene Bax. Bax is a promoter of the mitochondrial pathway that promotes the release of CytC, activates Caspase-3 and induces apoptosis of synoviocytes (27).…”
Section: Discussionmentioning
confidence: 99%
“…1 AFB1 exposure induces a decrease in L02 cell viability, oxidative stress, and apoptosis. a L02 cells were untreated (Ctrl) or treated with increasing concentrations of AFB1 (5,10,20,40,80, and 160 μM) for 24 h or with 40 μM AFB1 for the indicated time points (12,24,36,48,60, and 72 h); the cell viability was then detected by CCK-8 assay. b L02 cells were untreated (Ctrl) or treated with 40 μM AFB1 for 36 h. ROS production was detected by DCF probe staining and the percentage of DCF-positive hepatocytes was processed and quantified using ImageJ software (scale bar = 200 μm).…”
Section: Cav-1 Plays An Important Role In the Regulation Of Afb1inducmentioning
confidence: 99%
“…AFB1 can impair the antioxidant/prooxidant imbalance and elevate lipid peroxidation, resulting in the damage of biological molecules including lipids, proteins, and DNA in cellular systems 8 . The combination of these effects leads to the activation of a programmed cell death process or induces cells to produce potentially catastrophic genetic alterations, which depend on the dose and duration of AFB1 exposure 9,10 . A growing body of evidence has demonstrated that the detoxification of this toxin can generally be mediated by antioxidants, such as heme oxygenase-1 (HO-1), NAD(P)H/quinone oxidoreductase-1 (NQO1), and glutathione S-transferases (GSH), indicating the importance of oxidative stress regulation in AFB1induced hepatotoxicity 11 .…”
Section: Introductionmentioning
confidence: 99%